Раціональна кадрова політика як умова ефективного функціонування компанії в період кризи - Андрущенко, В. А. (Ways to Improve Construction Efficiency, 2014)
The article clarified the basic approaches to determining the nature of definitions of "crisis personnel management ", "concept of flexible personnel management," the analysis of theoretical approaches to the formation of a rational personnel policy of enterprises in modern conditions is made and experience of training for innovation and overcoming resistance to change from party personnel is generalized.